Mycetoma: An update - Relhan, Vineet; Mahajan, Khushbu; Agarwal, Pooja; Garg, VijayKumar (Indian journal of dermatology, 2017)
Mycetoma is a localized chronic, suppurative, and deforming granulomatous infection seen in tropical and subtropical areas. It is a disorder of subcutaneous tissue, skin and bones, mainly of feet, characterized by a triad of localized swelling, underlying sinus tracts, and production of grains or granules. Etiological classification divides it into eumycetoma caused by fungus, and actinomycetoma caused by bacteria. Since the treatment of these two etiologies is entirely different, a definite diagnosis after histopathological and microbiological examination is mandatory, though difficult. Serological test exists but is not so reliable; however, molecular techniques to identify relevant antigens have shown promise. The disease is notoriously difficult to treat. Eumycetoma may be unresponsive to standard antifungal therapy. Actinomycetoma responds to antibiotic therapy, but prolonged treatment is necessary. This review focuses on the etiopathogenesis, clinical features, laboratory diagnosis, and treatment of mycetoma.